2020
DOI: 10.15557/an.2020.0005
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal electromyography – a review of guidelines and current literature

Abstract: Celem artykułu jest przedstawienie aktualnych wytycznych dotyczących analizy oraz interpretacji zapisu badań elektromiograficznych krtani (laryngeal electromyography, LEMG) wraz z przeglądem głównych nurtów zastosowania EMG w praktyce otolaryngologiczno--foniatrycznej. Obecnie obowiązujące wytyczne zostały opracowane przez American Academy of Otolaryngology -Head and Neck Surgery w 2009 roku i przez European Laryngological Society w roku 2012. W zaleceniach obu towarzystw naukowych postuluje się zaadaptowanie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Review of the laryngeal electromyography (LEMG) literature showed that, initially, SEMG was not considered as an appropriate examination for laryngeal muscles [ 13 ]. Surface electrodes are noninvasive but the least selective electrode type, not suitable for recording details or electrical events associated with individual motor units.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the laryngeal electromyography (LEMG) literature showed that, initially, SEMG was not considered as an appropriate examination for laryngeal muscles [ 13 ]. Surface electrodes are noninvasive but the least selective electrode type, not suitable for recording details or electrical events associated with individual motor units.…”
Section: Discussionmentioning
confidence: 99%